ANTIBACTERIAL ACTIVITY Homotrigona apicalis PROPOLIS - Sari, Ayu Mitha; Kusuma, Irawan Wijaya; Yani, Sinar; Arung, Enos Tangke (Gorontalo Journal of Forestry Research, 2024)
Propolis is a resinous material that bees gather from specific plant exudate streams and utilize to build hives, caulk or seal crevices, create funnels for bees to enter, store honey and pollen, maintain a warm environment, and function as a natural antibacterial. One type of propolis from the Meliponini Tribe, Propolis Homotrigona Apicalis, is made from resin of the damar tree. This research aims to present scientific data on the effects of propolis as an antibacterial in the human gastrointestinal system. The parameters examined included qualitative phytochemical activity, Porphyromonas sp, Steptococcus sp, and Eschericia sp activity as measured by the minimum inhibitory concentration (MIC) using the agar well method on Mueller Hiton Agar (MHA) media, as well as testing for antibacterial potency and comparing its activity to that of a positive chloramphenicol control. Using the cold maceration technique, 96% EtOH solvent was used to extract propolis over the course of three 24-hour periods. Alkaloids, flavonoids, triterpenoids, and carbohydrates were all active, according to the findings of phytochemical tests. According to the findings of the activity test, Porphyromonas sp, Steptococcus sp, and Eschericia sp all exhibited antibacterial activity. Propolis Homotrigona Apicalis has the potential to be utilized as a treatment that treats diarhea, gum inflammation, and bad breath since it has antibacterial action in these areas as well as a healthy digestive system.